Effect of long-term cervical extensor exercise program on functional disability, pain intensity, range of motion, cervical muscle mass, and cervical curvature in young adult population with chronic non-specific neck pain: a randomized controlled trial - Yao Zhang; Wancheng Lin; Meng Yi; Jipeng Song; Lixiang Ding (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background The prevalence of chronic non-specific neck pain (CNNP) is on the rise among the young adult population. We herein aimed to compare the effects of long-term specific cervical extensor training and stretching exercises on improving this chronic disorder in young adults. Methods In this prospective, randomized, controlled study, 70 participants aged 18–35 years with CNNP and cervical lordosis loss were included. The participants were assigned to undergo either specific cervical extensor training (observation group) or perform usual stretching exercises (control group). The exercise duration was set at 12 months, with 9 months at the clinic and 3 months at home. The outcome assessments included changes in the neck disability index, visual analog scale from baseline, cervical range of motion (CROM), cross-sectional areas (CSAs) of cervical extensors, and cervical curvature from baseline. The outcome measures were compared between groups at 3, 6, and 12 months of follow-up. Results All 70 participants underwent randomization, and no significant differences in demographics and baseline data were found between the two groups. The observation group showed a greater improvement in neck disability index and visual analog scale scores at the 12-month follow-up than the control group. Additionally, a more substantial increase in CROM and CSAs of cervical extensors was observed in the observation group at the 6-month and 12-month follow-ups (P < 0.05). Although more participants in the observation group achieved cervical lordosis at the 12-month follow-up, the difference was marginally nonsignificant (9% in the control group vs. 28% in the observation group, P = 0.075). Conclusions In young adults with CNNP, long-term specific cervical extensor training was associated with a more significant clinically meaningful improvement in disability, pain, and CROM than stretching exercises. The increased CSAs of cervical extensors may potentially contribute to the restoration of cervical lordosis. Trial registration The study is registered at the Chinese domestic clinical trial (ChiCTR2000040009) at Chictr.org. The date of registration: November 18, 2020.